2014
DOI: 10.14740/jmc1977w
|View full text |Cite
|
Sign up to set email alerts
|

Down the Wrong Way: An Important Complication of Nasogastric Tube Placement

Abstract: Placement of a nasogastric tube is a very common procedure carried out by doctors and nurses on both medical and surgical wards. Indications include for feeding purpose to meet the patient's nutrition requirement and a therapeutic use to decompress a distended bowl in an acute small/large bowl obstruction. Insertion of a nasogastric tube into the pulmonary tree is a well-recognized complication that can possibly cause a pneumothorax or pulmonary aspiration if feeding was commenced without checking its position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Ocimum Scientific Publishers 10.33513/OJSC/1901-07Open Journal of Surgery Case Reports usually injured with a mortality rate reaching 0.3% (Table1)[2,[5][6][7][8][9]. Philip Ryom et al,[2] retrospectively studied periods1997-2001 and 2002-2005 and reported that nasogastric tube insertion was the cause of esophageal perforations which occurred at 8% and 3% rate, respectively.There are several factors contributing to the risk of nasogastric tube misplacement, such as several unsuccessful attempts or head and neck position (Table2)[8,10,11]. It is important to Nasogastric tube insertion complications (Levin tube).…”
mentioning
confidence: 99%
“…Ocimum Scientific Publishers 10.33513/OJSC/1901-07Open Journal of Surgery Case Reports usually injured with a mortality rate reaching 0.3% (Table1)[2,[5][6][7][8][9]. Philip Ryom et al,[2] retrospectively studied periods1997-2001 and 2002-2005 and reported that nasogastric tube insertion was the cause of esophageal perforations which occurred at 8% and 3% rate, respectively.There are several factors contributing to the risk of nasogastric tube misplacement, such as several unsuccessful attempts or head and neck position (Table2)[8,10,11]. It is important to Nasogastric tube insertion complications (Levin tube).…”
mentioning
confidence: 99%